2010
DOI: 10.1063/1.3353077
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic counter-rotating vortices and synergetic stabilizing effects of magnetic field and plasma flow

Abstract: A nonlinear two-dimensional steady state solution in the framework of hydrodynamics describing a row of periodic counter-rotating vortices is extended to the magnetohydrodynamic (MHD) equilibrium equation with incompressible flow of arbitrary direction. The extended solution covers a variety of equilibria because four surface quantities remain free. Similar to the case of the MHD cat-eyes equilibrium [Throumoulopoulos et al., J. Phys. A: Math. Theor. 42, 335501 (2009)] and unlike linear equilibria, the flow ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
(46 reference statements)
3
23
1
Order By: Relevance
“…The maximum of E takes larger values as the flow amplitude increases but its position is insensitive to the flow. For parallel flows application of a condition for linear stability implies that the equilibrium nonlinearity has a stabilizing effect together with a weaker stabilizing impact of the sheared flow in agreement with past nonlinear equilibrium studies [17,18,19]. Also even a small up-down asymmetry influences stability.…”
Section: Discussionsupporting
confidence: 84%
“…The maximum of E takes larger values as the flow amplitude increases but its position is insensitive to the flow. For parallel flows application of a condition for linear stability implies that the equilibrium nonlinearity has a stabilizing effect together with a weaker stabilizing impact of the sheared flow in agreement with past nonlinear equilibrium studies [17,18,19]. Also even a small up-down asymmetry influences stability.…”
Section: Discussionsupporting
confidence: 84%
“…• In certain cases stability is improved by the equilibrium nonlinearity in agreement with past equilibrium studies in plane geometry [15,16]. A pertinent example supporting this result in connection with the equilibrium of Fig.…”
Section: Stability Considerationsupporting
confidence: 72%
“…In particular, by including in the solution fourteen free parameters we have derived ITER-like equilibria with prescribed values of the safety factor on axis and toroidal beta for both Mach-function profiles, peaked on and off axis. Application of a sufficient condition for linear stability showed that this condition is satisfied only in a small region irrespective of flow and flow shear unlike the cases of the nonlinear cat-eyes [12] and counter-rotating-vortices equilibria [13]. This result is in favor to the conjecture that the equilibrium nonlinearity may activate flow stabilization.…”
supporting
confidence: 52%
“…Application of (16) for R in and R out furnishes relations (12) and (13). Relation (14) for the upper point can be derived in a similar way.…”
mentioning
confidence: 92%
See 1 more Smart Citation